1.7: Properties of Exponents
- Page ID
- 45002
\( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)
\( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)
\( \newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\)
( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\)
\( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\)
\( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\)
\( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\)
\( \newcommand{\Span}{\mathrm{span}}\)
\( \newcommand{\id}{\mathrm{id}}\)
\( \newcommand{\Span}{\mathrm{span}}\)
\( \newcommand{\kernel}{\mathrm{null}\,}\)
\( \newcommand{\range}{\mathrm{range}\,}\)
\( \newcommand{\RealPart}{\mathrm{Re}}\)
\( \newcommand{\ImaginaryPart}{\mathrm{Im}}\)
\( \newcommand{\Argument}{\mathrm{Arg}}\)
\( \newcommand{\norm}[1]{\| #1 \|}\)
\( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\)
\( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\AA}{\unicode[.8,0]{x212B}}\)
\( \newcommand{\vectorA}[1]{\vec{#1}} % arrow\)
\( \newcommand{\vectorAt}[1]{\vec{\text{#1}}} % arrow\)
\( \newcommand{\vectorB}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)
\( \newcommand{\vectorC}[1]{\textbf{#1}} \)
\( \newcommand{\vectorD}[1]{\overrightarrow{#1}} \)
\( \newcommand{\vectorDt}[1]{\overrightarrow{\text{#1}}} \)
\( \newcommand{\vectE}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash{\mathbf {#1}}}} \)
\( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)
\( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)
\(\newcommand{\avec}{\mathbf a}\) \(\newcommand{\bvec}{\mathbf b}\) \(\newcommand{\cvec}{\mathbf c}\) \(\newcommand{\dvec}{\mathbf d}\) \(\newcommand{\dtil}{\widetilde{\mathbf d}}\) \(\newcommand{\evec}{\mathbf e}\) \(\newcommand{\fvec}{\mathbf f}\) \(\newcommand{\nvec}{\mathbf n}\) \(\newcommand{\pvec}{\mathbf p}\) \(\newcommand{\qvec}{\mathbf q}\) \(\newcommand{\svec}{\mathbf s}\) \(\newcommand{\tvec}{\mathbf t}\) \(\newcommand{\uvec}{\mathbf u}\) \(\newcommand{\vvec}{\mathbf v}\) \(\newcommand{\wvec}{\mathbf w}\) \(\newcommand{\xvec}{\mathbf x}\) \(\newcommand{\yvec}{\mathbf y}\) \(\newcommand{\zvec}{\mathbf z}\) \(\newcommand{\rvec}{\mathbf r}\) \(\newcommand{\mvec}{\mathbf m}\) \(\newcommand{\zerovec}{\mathbf 0}\) \(\newcommand{\onevec}{\mathbf 1}\) \(\newcommand{\real}{\mathbb R}\) \(\newcommand{\twovec}[2]{\left[\begin{array}{r}#1 \\ #2 \end{array}\right]}\) \(\newcommand{\ctwovec}[2]{\left[\begin{array}{c}#1 \\ #2 \end{array}\right]}\) \(\newcommand{\threevec}[3]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \end{array}\right]}\) \(\newcommand{\cthreevec}[3]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \end{array}\right]}\) \(\newcommand{\fourvec}[4]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \\ #4 \end{array}\right]}\) \(\newcommand{\cfourvec}[4]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \\ #4 \end{array}\right]}\) \(\newcommand{\fivevec}[5]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \\ #4 \\ #5 \\ \end{array}\right]}\) \(\newcommand{\cfivevec}[5]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \\ #4 \\ #5 \\ \end{array}\right]}\) \(\newcommand{\mattwo}[4]{\left[\begin{array}{rr}#1 \amp #2 \\ #3 \amp #4 \\ \end{array}\right]}\) \(\newcommand{\laspan}[1]{\text{Span}\{#1\}}\) \(\newcommand{\bcal}{\cal B}\) \(\newcommand{\ccal}{\cal C}\) \(\newcommand{\scal}{\cal S}\) \(\newcommand{\wcal}{\cal W}\) \(\newcommand{\ecal}{\cal E}\) \(\newcommand{\coords}[2]{\left\{#1\right\}_{#2}}\) \(\newcommand{\gray}[1]{\color{gray}{#1}}\) \(\newcommand{\lgray}[1]{\color{lightgray}{#1}}\) \(\newcommand{\rank}{\operatorname{rank}}\) \(\newcommand{\row}{\text{Row}}\) \(\newcommand{\col}{\text{Col}}\) \(\renewcommand{\row}{\text{Row}}\) \(\newcommand{\nul}{\text{Nul}}\) \(\newcommand{\var}{\text{Var}}\) \(\newcommand{\corr}{\text{corr}}\) \(\newcommand{\len}[1]{\left|#1\right|}\) \(\newcommand{\bbar}{\overline{\bvec}}\) \(\newcommand{\bhat}{\widehat{\bvec}}\) \(\newcommand{\bperp}{\bvec^\perp}\) \(\newcommand{\xhat}{\widehat{\xvec}}\) \(\newcommand{\vhat}{\widehat{\vvec}}\) \(\newcommand{\uhat}{\widehat{\uvec}}\) \(\newcommand{\what}{\widehat{\wvec}}\) \(\newcommand{\Sighat}{\widehat{\Sigma}}\) \(\newcommand{\lt}{<}\) \(\newcommand{\gt}{>}\) \(\newcommand{\amp}{&}\) \(\definecolor{fillinmathshade}{gray}{0.9}\)Multiplication Properties
Recall from chapter 1 that \(5^{3}=5 \cdot 5 \cdot 5 .\) In the same way we have
\[x^{3}=x \cdot x \cdot x\nonumber\]
Perform the given operations:
- \(x^{3} \cdot x^{5}=\underbrace{x \cdot x \cdot x}_{=x^{3}} \cdot \underbrace{x \cdot x \cdot x \cdot x \cdot x}_{=x^{5}}=x^{8}\)
- \(\left(x^{3}\right)^{4}=x^{3} \cdot x^{3} \cdot x^{3} \cdot x^{3}=\underbrace{x \cdot x \cdot x} \cdot x \cdot x \cdot x \cdot \cdot \underbrace{x \cdot x \cdot x} \cdot x \cdot x \cdot x=x^{12}\)
- \((x \cdot y)^{4}=\underbrace{x \cdot y} \cdot \underbrace{x \cdot y} \cdot \underbrace{x \cdot y} \cdot \underbrace{x \cdot y}=x^{4} y^{4}\)
We can summarize these examples into the following useful rules:
For any integers \(n\) and \(m\)
- \(x^{n} x^{m}=x^{n+m}\)
- \((x^{n})^{m}=x^{nm}\)
- \((x y)^{n}=x^{n} y^{n}\)
Perform the given operation using the multiplication properties of exponents and write your answer in simplest form:
- \(b^{2} \cdot b^{3}=b^{2+3}=b^{5}\) (recall the meaning of exponents)
- \(x^{8} x^{7}=x^{8+7}=x^{15}\) (note that juxtaposition indicates multiplication)
- \(a^{8} a^{9} a^{14}=a^{8+9+14}=a^{31}\)
- \(4 x^{4} \cdot 7 x^{6}=(4 \cdot 7)\left(x^{4} \cdot x^{6}\right)=28 x^{10}\)
- \(5 x y^{3} \cdot 6 y=(5 \cdot 6)(x)\left(y^{3} \cdot y\right)=30 x y^{4}\)
- \(\left(5 x^{4} y^{2}\right)\left(2 x^{7} y^{3}\right)=10 x^{4+7} y^{2+3}=10 x^{11} y^{5}\)
- \((2 x)^{3}=2^{3} x^{3}=8 x^{3}\)
- \(\left(-4 a^{2} b^{5}\right)^{3}=(-4)^{3} a^{2 \cdot 3} b^{5 \cdot 3}=-64 a^{6} b^{15}\)
- \(\begin{align*}\left(-5 r^{3} s\right)^{2} \cdot\left(2 r^{4} s^{3}\right)^{3} \cdot\left(-r^{2} s^{2}\right) &=(-5)^{2} r^{3 \cdot 2} s^{2} \cdot 2^{3} r^{4 \cdot 3} s^{3 \cdot 3} \cdot(-1) r^{2} s^{2} \\&=25 r^{6} s^{2} \cdot 8 r^{12} s^{9} \cdot(-1) r^{2} s^{2} \\&=-200 r^{20} s^{13}\end{align*}\)
Division Properties
- \(\dfrac{x^{5}}{x^{3}}=\dfrac{x \cdot x \cdot x \cdot x \cdot x}{x \cdot x \cdot x}=\dfrac{x \cdot x}{1}=\dfrac{x^{2}}{1}=x^{2}\)
- \(\dfrac{x^{3}}{x^{5}}=\dfrac{x \cdot x \cdot x}{x \cdot x \cdot x \cdot x \cdot x}=\dfrac{1}{x \cdot x}=\dfrac{1}{x^{2}}\)
- \(\left(\dfrac{x}{y}\right)^{5}=\dfrac{x}{y} \cdot \dfrac{x}{y} \cdot \dfrac{x}{y} \cdot \dfrac{x}{y} \cdot \dfrac{x}{y}=\dfrac{x \cdot x \cdot x \cdot x \cdot x}{y \cdot y \cdot y \cdot y \cdot y}=\dfrac{x^{5}}{y^{5}}\)
We can summarize these examples into the following useful rules:
For any integers \(n\) and \(m\)
- \(\dfrac{x^{n}}{x^{m}}=x^{n-m}\)
- \(\left(\dfrac{x}{y}\right)^{n}=\dfrac{x^{n}}{y^{n}}\)
Perform the given operation using the division properties of exponents and state your answer in simplest form:
- \(\dfrac{b^{8}}{b^{7}}=b^{8-7}=b^{8+(-7)}=b^{1}=b\)
- \(\dfrac{x^{12} y^{2}}{x^{8} y}=x^{12-8} y^{2-1}=x^{12+(-8)} y^{2+(-1)}=x^{4} y^{1}=x^{4} y\)
- \(\dfrac{8 x^{6} y^{2}}{6 x^{5} y^{7}}=\dfrac{4 x^{6-5}}{3 y^{7-2}}=\dfrac{4 x^{1}}{3 y^{5}}=\dfrac{4 x}{3 y^{5}}\)
- \(\dfrac{\left(m^{2}\right)^{3}\left(n^{4}\right)^{5}}{\left(m^{3}\right)^{3}}=\dfrac{m^{6} n^{20}}{m^{9}}=\dfrac{n^{20}}{m^{3}}\)
- \(\left(\dfrac{3 a^{2} b^{4}}{9 c^{3}}\right)^{2}=\left(\dfrac{a^{2} b^{4}}{3 c^{3}}\right)^{2}=\dfrac{a^{2 \cdot 2} b^{4 \cdot 2}}{3^{2} c^{3 \cdot 2}}=\dfrac{a^{4} b^{8}}{9 c^{6}}\)Another way to simplify this correctly is this: \(\left(\dfrac{3 a^{2} b^{4}}{9 c^{3}}\right)^{2}=\dfrac{3^{2} a^{2 \cdot 2} b^{4 \cdot 2}}{9^{2} c^{3 \cdot 2}}=\dfrac{9 a^{4} b^{8}}{81 c^{6}}=\dfrac{a^{4} b^{8}}{9 c^{6}}\)
Zero Exponent
Recall from chapter 1 that \((-7)^{0}=1\) and \(8^{0}=1 .\) In the same way we have \(x^{0}=1\)
\(a^{0}=1 \nonumber\)
Evaluate
- \(15^{0}=1\)
- \((-15)^{0}=1\)
- \(-15^{0}=-1\)
- \((15 x)^{0}=1\)
- \(15 x^{0}=15 \cdot 1=15\)
Negative Exponents
For any integer \(n\)
- \(a^{-n}=\dfrac{1}{a^{n}}\)
- \(\dfrac{1}{a^{-n}}=a^{n}\)
- \(\left(\dfrac{a}{b}\right)^{-n}=\left(\dfrac{b}{a}\right)^{n}\)
Note 5.6. The negative exponent rules can be used to switch terms from numerator to denominator or vice versa, and is useful to write expressions using positive exponents only.
- \(\dfrac{x^{-3} y^{2}}{z^{4}}=\dfrac{y^{2}}{x^{3} z^{4}}\)
- \(\dfrac{x^{4}}{y^{-5} z^{2}}=\dfrac{x^{4} y^{5}}{z^{2}}\)
Perform the given operation and write your answer using positive exponents only
- \(\dfrac{x^{4} y^{2}}{x^{3} y^{-3}}=x^{4-3} y^{2-(-3)}=x^{4+(-3)} y^{2+3}=x y^{5}\)
- \(\left(x^{2} y\right) \cdot\left(x y^{-4}\right)=x^{2+1} y^{1+(-4)}=x^{3} y^{-3}=\dfrac{x^{3}}{y^{3}}\)
Simplify: \(\left(\dfrac{8 y}{3 x^{3}}\right)^{3}\)